Tunable Mid-Infrared Light Source Based on Difference Frequency Generation in Periodically Poled Lithium Niobate - Han, Ling (My University, 2007)
In this work, tunable Mid-Infrared (IR) light sources based on quasi-phase matched (QPM) difference frequency generation (DFG) by periodically poled lithium niobate (PPLN) crystals are studied. The theory of DFG and the characteristics of lithium niobate crystals are described and analyzed. Characteristics of the wavelength tuning of QPM DFG by PPLN crystals are studied. In order to analyze in detail, simulation and experimental data of the widely tunable mid-IR laser source around 2 1- μm to 5 1- μm wavelength are presented. The simulations of DFG process by PPLN are conducted based on the nonlinear optics reported. In the experiment, a 1.064 μm Nd:YAG laser and a tunable Ti:sapphire laser are employed as the signal and pump lasers, respectively. Based on the studies of the wavelength tuning characteristics at different temperatures, an optimization procedure to achieve a maximum wavelength tuning range is proposed. The potential applications in gas detection of the mid-IR source are also described briefly. Recommendation for future works and potential applications of the PPLN DFG based mid-IR lasers are discussed.
Keywords: Mid-Infrared Light; Lithium Niobate; difference frequency generation; periodically poled lithium niobate